Margret and H.A. Rey's Curious George and the puppies - Rey, Margret; Rey, H. A. 1898- (Hans Augusto) (Houghton Mifflin, 1998)
Curious George goes to the animal shelter where he accidentally lets all the dogs out of their cages and creates quite a ruckus.